Eating disorders in New Zealand: Implications for Māori and health service delivery. Issue 12 (31st August 2020) - Lacey, Cameron; Cunningham, Ruth; Rijnberg, Vivienne; Manuel, Jenni; Clark, Mau Te Rangimarie; Keelan, Karen; Pitama, Suzanne; Huria, Tania; Lawson, Rachel; Jordan, Jennifer
Abstract: Objective: Lifetime prevalence rates in Te Rau Hinengaro (The New Zealand Mental Health Survey) suggest eating disorders are at least as common in the Māori population as the non‐Māori population, yet little is known at a population level about those accessing specialist mental health treatment for eating disorders in New Zealand. The aim of this study was to describe the population undergoing specialist mental health treatment for eating disorders and compare Māori and non‐Māori clinical characteristics and service use. Method: This study uses the Programme for the Integration of Mental Health Data data set, managed by the New Zealand Ministry of Health to describe the characteristics of people with eating disorders and their use of specialist mental health services from 2009 to 2016. Results: There were 3, 835 individuals with a diagnosed eating disorder who had contact with specialist mental health services in this time period, 7% of whom were Māori. Within the cohort, Māori had a higher prevalence for a bulimia nervosa diagnosis, fewer diagnosed with anorexia nervosa, and a higher prevalence of other psychiatric comorbidity than non‐Māori. Discussion: There is discrepancy between the proportion of service users accessing specialist mental health services who are Māori and the assessed crude prevalence of eating disorders for Māori in national estimates. Once Māori are in specialist services; however, their use of services is comparable to non‐Māori. Further research is needed to highlight the experiences of those Māori with eating disorders and address barriers to accessing services for Māori with eating disorders.